Anticancer activity of the intraperitoneal-delivered DFP-10825, the cationic liposome-conjugated RNAi molecule targeting thymidylate synthase, on peritoneal disseminated ovarian cancer xenograft model - Iizuka K; Jin C; Eshima K; Hong MH; Eshima K; Fukushima M (Dove Medical Press, 2018)
Kenzo Iizuka, Cheng Jin, Kokoro Eshima, Mei Hua Hong, Kiyoshi Eshima, Masakazu Fukushima Division of Research and Development, Delta-Fly Pharma Inc., Tokushima, Japan Introduction: Peritoneal disseminated ovarian cancer is one of the most difficult cancers to treat with conventional anti-cancer drugs and the treatment options are very limited, although an intraperitoneal (ip) paclitaxel has shown some clinical benefit. Therefore, treatment of peritoneal disseminated ovarian cancer is a highly unmet medical need and it is urgent to develop a new ip delivered drug regulating the fast DNA synthesis. Methods: We developed a unique RNAi molecule consisting of shRNA against the thymidylate synthase (TS) and a cationic liposome (DFP-10825) and tested its antitumor activity and PK profile in peritoneally disseminated human ovarian cancer ascites models by the luciferase gene-transfected SCID mice. DFP-10825 alone, paclitaxel alone or combination with DFP-10825 and paclitaxel were administered in an ip route to the tumor-bearing mice. The TS expression level was measured by conventional RT-PCR. The anti-tumor activity and host survival benefit by DFP-10825 treatment on tumor-bearing mice were observed as resulting from the specific TS mRNA knock-down in tumors. Results: DFP-10825 alone significantly suppressed the growth of SKOV3-luc tumore ascites cells and further extended the survival time of these tumor-bearing mice. Combination with the ip paclitaxel augmented the antitumor efficacy of DFP-10825 and significantly prolonged the survival time in the tumor-bearing mice. Short-hairpin RNA for TS (TS shRNA) levels derived from DFP-10825 in the ascetic fluid were maintained at a nM range across 24 hours but not detected in the plasma, suggesting that TS shRNA is relatively stable in the peritoneal cavity, to be able to exert its anti-tumor activity, but not in blood stream, indicating little or no systemic effect. Conclusion: Collectively, the ip delivery of DFP-10825, TS shRNA conjugated with cationic liposome, shows a favorable antitumor activity without systemic adverse events via the stable localization of TS shRNA for a sufficient time and concentration in the peritoneal cavity of the peritoneally disseminated human ovarian cancer-bearing mice. Keywords: DFP-10825, thymidylate synthase, short-hairpin RNA, cationic liposome, ip delivery, intraperitoneal dissemination, ovarian cancer